Epidemiological profile and survival of chest trauma victims cared at a public hospital in Sergipe State (Research, Society and Development, 2021)
Introduction: Chest trauma consists of a physical shock with a strong impact that causes damage of varying extent in the body. Objective: To assess the epidemiological profile and survival of chest trauma victims, associated or not with polytrauma, using the TRISS and TRISS-like severity indexes. Methods: Observational, prospective, quantitative study of thoracic trauma victims who entered the emergency department of a hospital in the state of Sergipe. An instrument with physiological and sociodemographic data about topography and clinical information was used. Mann Withney, Fisher, Pearson's Chi-square, Pearson's Chi-square tests with Monte-Carlo simulations were used, considering significant when p